Analysis of Factors Affecting the Quality of Life of STEMI Patients with Primary Percutaneous Coronary Intervention (PPCI) - Jenal Abidin; Saifurrohman Saifurrohman; Heri Kristianto (Universitas Aisyah Pringsewu, 2023)
Objective: To describe the published literature on Factors Affecting the Quality of Life of STEMI Patients Undergoing Primary Percutaneous Coronary Intervention (PPCI). Design: Scooping review. Methods: Searching for literature from several databases such as ProQuest, ScienceDirect, and Google Scholar; then, the articles are identified with the PRISMA flow. Data were extracted on the author, year, research method, setting, sample size, reported factors, and quality of life questionnaire used. Results: A literature search from the database yielded a total of 987 literature and 12 research articles that matched the inclusion criteria. Six factors affecting the quality of life of STEMI patients with Primary Percutaneous Coronary Intervention (PPCI): (a) STEMI, (b) age, (c) gender, (d) Killip, (e) GRACE, (f) coronary lesions, (g) disease: DM and HT.